2019
DOI: 10.1021/jacs.9b12629
|View full text |Cite
|
Sign up to set email alerts
|

Thiol–Chromene “Click” Reaction Triggered Self-Immolative for NIR Visualization of Thiol Flux in Physiology and Pathology of Living Cells and Mice

Abstract: Understanding the pathological process of biological systems can greatly improve the prevention and treatment of diseases. The study of pathological processes has now reached the molecular level, and molecular fluorescent probes have become a powerful tool. Chromene, also known as benzo-pyran molecule, is a structural element of natural products with good biological compatibility and was developed as a fluorescent probe. The thiol−chromene "click" nucleophilic pyran ring-opening reaction allows the quick detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(71 citation statements)
references
References 40 publications
1
68
0
Order By: Relevance
“…To test the application of biological experiments, we first carried out cytotoxicity experiments according to literature methods [ [46] , [47] , [48] , [49] ]. The results showed that the cells survival rate was more than 85 % (CCK-8 method), indicating that the probe AI had the future to be applied into cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test the application of biological experiments, we first carried out cytotoxicity experiments according to literature methods [ [46] , [47] , [48] , [49] ]. The results showed that the cells survival rate was more than 85 % (CCK-8 method), indicating that the probe AI had the future to be applied into cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since their discovery, fluorescent probes have been engineered to accurately monitor and quantify in real-time an increasing variety of physiological parameters in living cells such as ion concentration variations [1] , cysteines [2] , pH [3] , enzymatic activity [4] or oxidative stress [5] , [6] , [7] , [8] , but also various cellular compounds [9] , [10] , [11] , [12] . Genetically-encoded fluorescent proteins are of particular interest as they can be addressed to specific organelles, such as the nucleus or the mitochondria, allowing a subcellular resolution [13 , 14] .…”
Section: Methods Detailsmentioning
confidence: 99%
“…In 2020, Yutao Yang et al [137] developed a NIR fluorescent probe (NIR-HMPC, Probe 41, Figure 36) based on a Michael addition reaction followed by self-immolative reaction to selectively detect mitochondrial thiols. This NIR probe made by conjugating hemicyanine dye with a benzopylium was connected with a 7-hydroxymethyl-2,3-dihydro-1H-cyclopent-a[b]chromene-1-one with a carbonyl ester.…”
Section: Detection Of Mitochondrial Thiols Via a Michael Addition Reactionmentioning
confidence: 99%